Formulae of roughness peak distribution parameters with standard deviation and correlation length. (December 2015) - Zhou, Wei; Tang, Jinyuan; He, Yanfei
Principle error exists when peak distribution parameters are calculated based on the random process theory, and the microtopography simulation with desired peak distributions still cannot be realized. To solve these problems, the relationship between peak distribution parameters and surface statistical distribution parameters is studied through lots of rough surface reconstructions. The effects of high-pass filtering with different cut-off lengths are analyzed. In addition, formulae of peak distribution parameters with standard deviation and correlation length are constructed by mathematical fitting. The formulae are verified with experimental data and compared with classical literature. Finally, an example of application of the formulae to microtopography simulation is provided.